2022
DOI: 10.1093/cdn/nzac039
|View full text |Cite
|
Sign up to set email alerts
|

Health Mothers’ Groups in Nepal: Barriers, Facilitators, and Recommendations

Abstract: Background Nepal's female community health volunteers (FCHVs) each lead a monthly health mothers’ group (HMG) to share health-related information and engage communities in the health system. Suaahara II (SII), a United States Agency for International Development-funded multisectoral nutrition program, uses social and behavior change interventions to promote HMG participation and uses its health systems interventions to strengthen HMG quality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Overall, these findings underscore the program’s potential to foster positive social change by empowering participants with knowledge and skills that can enhance their lives and contribute to the well-being of their communities. Of these, one of the studies reported that participatory women’s literacy groups were found to be effective in improving maternal and child health outcomes, along with other benefits such as increased knowledge and empowerment of family members [ 56 ]. Education programs like this can serve as effective tools in improving maternal and child health knowledge among underprivileged rural women, potentially contributing to reducing maternal and neonatal mortality rates in Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these findings underscore the program’s potential to foster positive social change by empowering participants with knowledge and skills that can enhance their lives and contribute to the well-being of their communities. Of these, one of the studies reported that participatory women’s literacy groups were found to be effective in improving maternal and child health outcomes, along with other benefits such as increased knowledge and empowerment of family members [ 56 ]. Education programs like this can serve as effective tools in improving maternal and child health knowledge among underprivileged rural women, potentially contributing to reducing maternal and neonatal mortality rates in Nepal.…”
Section: Discussionmentioning
confidence: 99%